Pack dogs in the Canadian Arctic - MacPherson, A. H.; Manning, T. H. (Polar Record, 1961)
Before the Eskimo economy had been much affected by the advent of whites, pack dogs were a common means of summer transport in most if not all parts of the Canadian Arctic. Among the changes which have led to less inland movement in summer are the attraction of settlements at “ship time”, the increase in bulk and weight of the average Eskimo family's personal effects, the increased reliance on bought food, the advent of boats and modern weapons, and the decline of the mainland caribou. Also, the availability of steel-shod dog sledges and the increased size of dog teams have, in some areas, made it more convenient to use a sledge in summer than to use pack dogs. However, sledge travel is not suitable for a small party of whites on a single summer trip, as a large team is needed and sufficient dogs and dog food may be difficult to obtain. We have found the use of pack dogs both convenient and economical, particularly for reconnaissance work, where freedom to spend varying amounts of time in any place along the route is a requisite. The reduction of weight of one's personal pack increases the pleasure of travelling and facilitates work along the way. We have used from one to four dogs, depending on their availability and upon the amount of dog food which can be obtained before starting and en route. Five is probably the maximum number of pack dogs that a man travelling alone would want to look after, as loading in the morning and adjusting packs during the day are time-consuming tasks.